2011
DOI: 10.1371/journal.pone.0028077
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hedgehog Signaling Antagonizes Serous Ovarian Cancer Growth in a Primary Xenograft Model

Abstract: BackgroundRecent evidence links aberrant activation of Hedgehog (Hh) signaling with the pathogenesis of several cancers including medulloblastoma, basal cell, small cell lung, pancreatic, prostate and ovarian. This investigation was designed to determine if inhibition of this pathway could inhibit serous ovarian cancer growth.MethodologyWe utilized an in vivo pre-clinical model of serous ovarian cancer to characterize the anti-tumor activity of Hh pathway inhibitors cyclopamine and a clinically applicable deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 27 publications
1
53
0
1
Order By: Relevance
“…Hence, a correlation between Hedgehog ligand expression and clinical benefit could not be determined. There are several possible explanations for why fewer patients on this study seemed to have Hedgehog ligand overexpression compared with prior studies (19,21) conducted on banked tumor specimens. For example, it is possible that Hedgehog ligand overexpression is associated with chemotherapy resistance that could prevent patients from achieving CR (and therefore being eligible for this study).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Hence, a correlation between Hedgehog ligand expression and clinical benefit could not be determined. There are several possible explanations for why fewer patients on this study seemed to have Hedgehog ligand overexpression compared with prior studies (19,21) conducted on banked tumor specimens. For example, it is possible that Hedgehog ligand overexpression is associated with chemotherapy resistance that could prevent patients from achieving CR (and therefore being eligible for this study).…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, excessive or inappropriate expression of the Hedgehog ligand has been implicated in the pathogenesis of other sporadic cancers including pancreatic and other gastrointestinal, prostate, lung, and ovarian cancers (14)(15)(16)(17)(18)(19). Recent studies have shown a paracrine mechanism of Hedgehog pathway activation in some tumor types, wherein Hedgehog ligand secreted by tumor cells acts on neighboring stromal cells, subsequently contributing to tumorigenesis ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of Hh signalling decreased spherogenicity in CD133+ glioma CSCs, decreased self-renewal in Aldefluor+ B-ALL cells, and inhibited clonogenicity of multiple myeloma CSCs [121,122]. In addition to depleting Aldefluor+ cells, Hh inhibition also decreased metastatic spread in a xenograft model of pancreatic cancer and inhibited the growth of human serous ovarian tumor xenografts [123,124].…”
Section: Targeting Hedgehog Signallingmentioning
confidence: 99%